2021
DOI: 10.1093/ajhp/zxab218
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing preoperative antibiotics in patients with β-lactam allergies: A role for pharmacy

Abstract: Disclaimer In an effort to expedite the publication of articles related to the COVID-19 pandemic, AJHP is posting these manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…The results of this study add evidence to the increasing literature that demonstrates the positive impact of penicillin allergy de-labeling interventions. Several previous studies have also shown an increase in first-line antibiotic use following pharmacist-led penicillin allergy efforts [6,8,16]. Our study was similar to the study by Kwiatkowski et al in terms of study design and endpoints but differed in key aspects of methodology, including the patient population included, the identification of appropriate patients, the timing of interviews, and making formal antibiotic therapy recommendations to providers.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The results of this study add evidence to the increasing literature that demonstrates the positive impact of penicillin allergy de-labeling interventions. Several previous studies have also shown an increase in first-line antibiotic use following pharmacist-led penicillin allergy efforts [6,8,16]. Our study was similar to the study by Kwiatkowski et al in terms of study design and endpoints but differed in key aspects of methodology, including the patient population included, the identification of appropriate patients, the timing of interviews, and making formal antibiotic therapy recommendations to providers.…”
Section: Discussionsupporting
confidence: 73%
“…Pharmacists assessed penicillin allergies via telephone and then made antibiotic recommendations to providers to increase first-line preoperative antibiotic use. The study found that cefazolin use significantly increased from 28% to 65% after the implementation of this intervention (p = 0.001) [8]. The above study demonstrates that pharmacists are able to assess patients' allergy history and assist providers in appropriate antibiotic selection in patients with documented penicillin allergies.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…One reason could be that infection control is often achieved through an integrated approach involving different professionals [ 11 ]. However, various pharmacist-led initiatives have been reported to promote the use of antimicrobial agents, improve achievement rate of effective blood concentration range in vancomycin (VCM) therapy [ 12 ], reducing the rate of MRSA in intensive care units and in antimicrobial allergic reactions [ 13 16 ]. In addition, a retrospective study has shown that the survival rate at 30 days after starting VCM therapy with pharmacist-led VCM initial dose planning was higher than that of non-intervention groups in MRSA bacteremia patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%